2018
DOI: 10.1111/tid.12988
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and infection risk in kidney transplant recipients: A single‐center cohort study

Abstract: Vitamin D status influences the risk of infection among KT recipients, with the association being particularly evident for opportunistic events and mainly restricted to the early post-transplant period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
(91 reference statements)
1
7
1
Order By: Relevance
“…Notably, also in an additional analysis of opportunistic infections, we could not detect an association with vitamin D status (Table S1). These findings are in line with the results of Ban Th et al Few studies, most of them based on retrospective data collection, reported an association between vitamin D deficiency and infections . The cutoff value used for definition of vitamin D deficiency in our study is based on studies that considered dynamics in bone turnover variables .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Notably, also in an additional analysis of opportunistic infections, we could not detect an association with vitamin D status (Table S1). These findings are in line with the results of Ban Th et al Few studies, most of them based on retrospective data collection, reported an association between vitamin D deficiency and infections . The cutoff value used for definition of vitamin D deficiency in our study is based on studies that considered dynamics in bone turnover variables .…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in line with the results of Ban Th et al 20 Few studies, most of them based on retrospective data collection, reported an association between vitamin D deficiency and infections. 4,6,21 The cutoff value used for definition of vitamin D deficiency in our study is based on studies that considered dynamics in bone turnover variables. 11 Up to now, no cutoff has been specifically established for infectious risk stratification by vitamin D status.…”
Section: Discussionmentioning
confidence: 99%
“…Infection is a major cause for death after KT. Several recent reports established negative correlation between VD status and infection risk, especially for cytomegalovirus and BK virus infections in KTRs [91,92]. However, our observational study showed no association between VD status and prevalence of urinary tract infections after KT [93].…”
Section: Vd Pleiotropy After Kt: Infectioncontrasting
confidence: 72%
“…Since vitamin D regulates the immune system, alteration in its level affects the outcome of allografts, e.g., acute cellular rejection (ACR) and infection [ 39 ]. Similarly, several other studies reported that transplanted patients have a higher risk of infections [ 36 , 37 , 167 , 168 , 169 ] and rejections [ 38 , 170 ]. Thus, vitamin D supplementation and tight follow-up of its level is important in transplant recipient patients [ 39 ].…”
Section: Vitamin D and Sirt1 In Relation To Non-communicable Diseases...mentioning
confidence: 70%
“…Many of these are associated with a reduced level of SIRT1 as well [ 34 , 35 ]. Vitamin D levels may influence the risk of infections in kidney and liver transplant recipients [ 36 , 37 ] and the risk of acute rejection [ 38 , 39 ] and of new-onset diabetes after kidney transplantation [ 40 ].…”
Section: Introductionmentioning
confidence: 99%